2016
DOI: 10.1002/anie.201603556
|View full text |Cite
|
Sign up to set email alerts
|

Highly Tunable Selectivity for Syngas‐Derived Alkenes over Zinc and Sodium‐Modulated Fe5C2 Catalyst

Abstract: Zn- and Na-modulated Fe catalysts were fabricated by a simple coprecipitation/washing method. Zn greatly changed the size of iron species, serving as the structural promoter, while the existence of Na on the surface of the Fe catalyst alters the electronic structure, making the catalyst very active for CO activation. Most importantly, the electronic structure of the catalyst surface suppresses the hydrogenation of double bonds and promotes desorption of products, which renders the catalyst unexpectedly reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
285
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(293 citation statements)
references
References 46 publications
8
285
0
Order By: Relevance
“…The development of complex oxides supported iron (or cobalt) nanocomposites may be promising to better fit the steam conditions of FTO and FTS . Selectivity modulation of CO hydrogenation by special element attracts great attentions . Since the beginning of 2015, we have demonstrated that spinel‐type supported cobalt catalysts are tolerant against sulfur poisons and steam during CO hydrogenation .…”
Section: Introductionmentioning
confidence: 99%
“…The development of complex oxides supported iron (or cobalt) nanocomposites may be promising to better fit the steam conditions of FTO and FTS . Selectivity modulation of CO hydrogenation by special element attracts great attentions . Since the beginning of 2015, we have demonstrated that spinel‐type supported cobalt catalysts are tolerant against sulfur poisons and steam during CO hydrogenation .…”
Section: Introductionmentioning
confidence: 99%
“…[35] Consequently,e thylene hydrogenation was conducted to compare the hydrogenation ability of alkenes on in situ prepared c-Fe 5 C 2 and q-Fe 3 C. Ap eak area ratio of ethane ( Figure S14) for c-Fe 5 C 2 is weaker than that for q-Fe 3 C (peak area ratio of c-Fe 5 C 2 to q-Fe 3 Ci s2 5:60), which demonstrates the weaker hydrogenationa bility for c-Fe 5 C 2 .I na ddition, Pham et al [36] calculated the effective barrier (DE eff )o fC 1 -C 1 coupling over c-Fe 5 C 2 and found that higher DE eff represented lower selectivity to long-chain hydrocarbons.E mit et al [26] found that the c-Fe 5 C 2 surface exhibited ah igher DE eff than q-Fe 3 C. Furthermore, CO 2 -TPD profiles ( Figure S15) indicate that q-Fe 3 Cs hows as tronger CO 2 adsorption capability and greater chain growth probability than c-Fe 5 C 2 .F or these reasons, c-Fe 5 C 2 may suppress the secondary hydrogenation of alkenes and accelerates alkened esorption, which lead to ah igh selectivity to short-chain alkenes;w hile q-Fe 3 Cs hows ah igher C 5 + In summary,u sing operando techniques complemented with well-designed experiments,t he structure evolution and structure-performance relationship of iron-based catalysts during CTH have been elaborated by conducting as ystematically comparative study for a-Fe 2 O 3 and g-Fe 2 O 3 .S pecifically, we have demonstrated that the generation of c-Fe 5 C 2 and q-Fe 3 Cf rom a-Fe 2 O 3 and g-Fe 2 O 3 ,r espectively,s houldb er esponsible for the performance deviation for two catalysts.F urthermore, experiments show that the highers electivity to lower olefins on c-Fe 5 C 2 is due to its highere ffective barrier,b ut weaker alkenes hydrogenationa bility.T he high selectivity to C 5 + hydrocarbonso nq-Fe 3 Ci sm ainly attributed to its strong CO 2 adsorption, which can enhancet he chain-growtho fa dsorbedc arbonaceous species. [35] Consequently,e thylene hydrogenation was conducted to compare the hydrogenation ability of alkenes on in situ prepared c-Fe 5 C 2 and q-Fe 3 C. Ap eak area ratio of ethane ( Figure S14) for c-Fe 5 C 2 is weaker than that for q-Fe 3 C (peak area ratio of c-Fe 5 C 2 to q-Fe 3 Ci s2 5:60), which demonstrates the weaker hydrogenationa bility for c-Fe 5 C 2 .I na ddition, Pham et al [36] calculated the effective barrier (DE eff )o fC 1 -C 1 coupling over c-Fe 5 C 2 and found that higher DE eff represented lower selectivity to long-chain hydrocarbons.E mit et al [26] found that the c-Fe 5 C 2 surface exhibited ah igher DE eff than q-Fe 3 C. Furthermore, CO 2 -TPD profiles ( Figure S15) indicate that q-Fe 3 Cs hows as tronger CO 2 adsorption capability and greater chain growth probability than c-Fe 5 C 2 .F or these reasons, c-Fe 5 C 2 may suppress the secondary hydrogenation of alkenes and accelerates alkened esorption, which lead to ah igh selectivity to short-chain alkenes;w hile q-Fe 3 Cs hows ah igher C 5 + In summary,u sing operando techniques complemented with well-designed experiments,t he structure evolution and structure-performance relationship of iron-based catalysts during CTH have been elaborated by conducting as ystematically comparative study for a-Fe 2 O 3 and g-Fe 2 O 3 .S pecifically, we have demonstrated that the generation of c-Fe 5 C 2 and q-Fe 3 Cf rom a-Fe 2 O 3 and g-Fe 2 O 3 ,r espectively,s houldb er esponsible for the performance deviation for two...…”
mentioning
confidence: 99%
“…The performance of iron catalysts can be greatly improved by adding “electronic” or chemical promoters to the catalyst formula . Among such promoters, potassium, sodium, copper, and manganese have been proposed. Recently, the TPR‐EXAFS technique confirmed that doping FTS catalysts with copper and alkali metals remarkably promotes the carburization rate relative to the undoped catalyst.…”
Section: Introductionmentioning
confidence: 99%